Clean hydrogen roadmap: Is greater realism leading to more credible paths forward? - Martin Lambert (The Oxford Institute for Energy Studies, 2023)
The Oxford Institute for Energy Studies started researching the role of hydrogen in the energy transition in 2020. Since then the interest in hydrogen has continued to grow globally across the energy industry. A key research question has been the extent to which clean hydrogen can be scaled up at reasonable cost and whether it can play a significant role in the global energy system. In April 2022, OIES launched a new Hydrogen Research Programme under the overarching theme of 'building business cases for a hydrogen economy'. This overarching theme was selected based on the observation that most clean hydrogen developments to date had been relatively small-scale pilot or demonstration projects, typically funded by government grants or subsidies. For clean hydrogen to play a significant role there will need to be business cases developed in order to attract the many hundreds of billions of dollars of investment required, most of which will need to come from the private sector, albeit ultimately underpinned by government-backed decarbonisation policies. Just over a year has passed since the start of the Hydrogen Research Programme, and the intention of this paper is to pull together key themes which have emerged from the research so far and which can form a useful framework for further research, both by OIES and others. The six key themes in this paper, listed below, are intended to create a framework to at least start to address the challenges: Hydrogen is in competition with other decarbonisation alternatives. The business case for clean hydrogen relies on government policy to drive decarbonisation. It is essential to understand emissions associated with potential hydrogen investments. Hydrogen investments need to consider the full value chain and its geopolitics. Transport of hydrogen is expensive and so should be minimised. Storage of hydrogen is an essential part of the value chain and requires more focus.
Keywords: 330; Energy Transition; Government Policy; Hydrogen; Value Chain